2005
DOI: 10.1017/s0953756205002388
|View full text |Cite
|
Sign up to set email alerts
|

The beetle gut: a hyperdiverse source of novel yeasts

Abstract: We isolated over 650 yeasts over a three year period from the gut of a variety of beetles and characterized them on the basis of LSU rDNA sequences and morphological and metabolic traits. Of these, at least 200 were undescribed taxa, a number equivalent to almost 30% of all currently recognized yeast species. A Bayesian analysis of species discovery rates predicts further sampling of previously sampled habitats could easily produce another 100 species. The sampled habitat is, thereby, estimated to contain well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
154
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(165 citation statements)
references
References 16 publications
(15 reference statements)
2
154
0
4
Order By: Relevance
“…Abe et al (2010) have described the presence of T. mycotoxinivorans in fresh shavings of palm tissue that were damaged by beetle larvae (Coleoptera: Dryophthoridae) in Japan. It occurrence was also described in grape marc in southern Peloponnese, Greece, by Ntougias et al (2010), which reports it as closely related to an unidentified member of Trichosporon clade, isolated from the xylophagous beetle Phrenapetes bennetti (Tenebrionidae), collected in Panama by Suh et al (2005). Hickey et al (2009) have found T. mycotoxinivorans to be a novel respiratory pathogen in patients with cystic fibrosis.…”
Section: Resultsmentioning
confidence: 91%
“…Abe et al (2010) have described the presence of T. mycotoxinivorans in fresh shavings of palm tissue that were damaged by beetle larvae (Coleoptera: Dryophthoridae) in Japan. It occurrence was also described in grape marc in southern Peloponnese, Greece, by Ntougias et al (2010), which reports it as closely related to an unidentified member of Trichosporon clade, isolated from the xylophagous beetle Phrenapetes bennetti (Tenebrionidae), collected in Panama by Suh et al (2005). Hickey et al (2009) have found T. mycotoxinivorans to be a novel respiratory pathogen in patients with cystic fibrosis.…”
Section: Resultsmentioning
confidence: 91%
“…For these purposes faecal or digesta samples have been collected from large animals (Urubschurov et al, 2008; or whole intestines from e.g. insects have been dissected (Suh et al, 2004b;2005a;Nguyen et al, 2007). Whereas rain worms, termites or other small animals can provide the whole GIT for the studies, only part of contents of wall of the GIT can be studied in large animals.…”
Section: Methods For Investigating Biodiversity Of the Yeasts From Gitmentioning
confidence: 99%
“…It thereby underlined the impact of the host and/or environmental factors on the yeasts diversity. Nevertheless, examination of yeasts harbouring the GIT of beetles from 27 families reviled a huge variety of yeasts (Suh et al, 2005a During three-years-period, Suh et al (2005a) isolated about 650 yeasts from the gut of diverse beetles collected from the south-eastern USA and Panama. Sequence analyses of the D1&D2 domains of LSU rRNA gene revealed 290 single species belonging to at least 27 taxa ( Fig.…”
Section: Yeasts In the Digestive Tract Of Beetlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some are normal flora on skin surfaces; others are parasitic or symbiotic and are mostly common in environments where there is a sugar-rich material. Some are associated with soil and insects [7,8].…”
Section: Introductionmentioning
confidence: 99%